Association Between VISTA and Vascular Cognitive Impairment in Older Chinese Adults: A Cross-Sectional Study - Liu D; Chi LJ (Clinical Interventions in Aging)
Dan Liu, Li-Jun Chi Department of Neurology, The First Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of ChinaCorrespondence: Li-Jun Chi, Department of Neurology, The First Affiliated Hospital of Harbin Medical University, No. 23 Postal Street, Nangang District, Harbin, Heilongjiang Province, People’s Republic of China, Email clj3751@163.comPurpose: Vascular cognitive impairment(VCI) ranks as the second most prevalent type of dementia.Increasing evidence has shown that inflammation and multi-faceted neuro-immune interactions integrate systemic and central inflammatory pathways, thereby inducing vascular tissue injury and contributing to the development of vascular cognitive impairment (VCI).V-type immunoglobulin-like suppressor of T cell activation (VISTA) is an Negative checkpoint regulators(NCR) that is associated with CNS homeostasis, interactions with peripheral immunity and CNS inflammation.The primary objective of this study was to seek the correlation between VISTA and VCI in patients with cardiovascular risk factors.Our secondary objective was to explore the potential of VISTA as a biomarker for VCI.Patients and Methods: We enrolled individuals with cardiovascular risk factors in this cross-sectional study research and categorized them into two groups: without cognitive impairment (control) and with cognitive impairment (VCI). VISTA expression in peripheral blood mononuclear cells (PBMCs) was analyzed using relative quantitative polymerase chain reaction. VISTA expression was identified in monocyte subsets using flow cytometry. We use Enzyme linked immunosorbent assay to detect inflammatory factors in serum.Results: In PBMC in patients with VCI, the expression of VSIR was significantly reduced. In contrast to controls, fasting glucose, fibrosis, and the levels of interleukin 6 (IL-6) in VCI patients were noticeably higher, and uric acid levels were significantly lower. Vsir mRNA expression in PBMCs correlated negatively with IL-6 levels, Trail Making Test B scores, and Hachinski scores and positively with Boston Naming Test scores. In intermediate monocytes, flow cytometry showed reduced Vsir expression, which was connected with VCI. The percentage of intermediate monocytes, uric acid, and the VISTA mean fluorescence intensity on intermediate monocytes were shown to be independent factors to VCI by multivariate logistic regression analysis.Conclusion: Decreased VISTA promotes the occurrence of VCI in patients with cardiovascular risk factors by promoting monocytes toward the proinflammatory intermediate monocyte subset. VISTA may serve as a potential biomarker for distinguishing VCI in individuals with cardiovascular risk factors.Keywords: neuroinflammation, intermediate monocyte, biomarker, flow cytometry